A novel intrauterine barrier for preventing the recurrence of IUA after TCRA procedure. (October 2022) - Chen, Meixia; Yuan, Liwei; Jin, He; Djurist, Ngenzi Richard; Zhang, Xueyu; Liu, Dan
Abstract: Intrauterine adhesion (IUA) is the result of abnormal endometrium repair after trauma and infection that damages the basal layer of the endometrium, which is then replaced by scar tissue. In such instances, the endometrium partially or completely loses the ability to conceive the embryo. Even after surgery-based comprehensive treatment, a high rate of adhesion remains. A thin endometrium, poor blood supply, and poor function may also lead to refractory infertility, resulting in a poor reproductive prognosis even when the uterine cavity has been completely restored to normal. Therefore, two key points of postoperative management are the use of an intrauterine barrier to prevent re-adhesion and medicine to promote endometrial repair. However, there is currently no clinically applicable barrier that can meet the personalized dimensions of uterine cavity shape and size or effectively separate the wound wall. We have designed an intrauterine barrier that consists of a unique uterine-shaped, estrogen-release intrauterine device (IUD), which can be combined with an injectable, temperature-sensitive hydrogel. For this study, we will insert an estrogen-release IUD into the uterine cavity following transcervical resection of adhesion (TCRA) surgery, at the same time injecting 3–5 mL of liquid hydrogel at room temperature into the uterine cavity via the cervical channel. Due to its temperature sensitivity, the hydrogel will gradually solidify into a jellylike consistency, filling the uterine cavity with a solid barrier and completely preventing contact with the wounded wall to avoid the recurrence of adhesion. The estrogen-release IUD will be wrapped in the hydrogel barrier, which has many pores that allow sustainable estrogen release to promote endometrial regeneration and repair. This protocol can meet the needs of postoperative management of TCRA, but experimental and clinical studies are still needed to demonstrate its effectiveness. If patients in the study group have a lower adhesion recurrence and higher pregnancy rate compared to controls, our hypothesis will be confirmed that this barrier will prove a clinical application to help the functional repair of the endometrium and achieve a good reproductive prognosis.